2020
DOI: 10.1177/0145561320927912
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Malignancy in Salivary Gland Tumors by a New Cytology Reporting System

Abstract: Objectives: The aim of this study was to analyze the risk of malignancy in salivary gland tumors on the basis of the Milan System for Reporting Salivary Gland Cytopathology. Methods: A retrospective review was performed of the charts of patients with salivary gland tumors in whom the final diagnosis was confirmed by surgical excision. Preoperative fine needle aspiration results were categorized according to the Milan System for Reporting Salivary Gland Cytopathology: non-diagnostic (category I), nonneoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Another important issue is that the diagnosis of cytology depends on the experience of pathologists and has the inter-institutional variability. Although the risk of malignancy (ROM) of AUS (atypia of undetermined significance) in the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) was only 20%, several studies showed that their ROM of AUS was higher than 20%, around 47–50% [ 15 , 16 , 17 ]. Before the proposal of Milan system, the ROM of cytological report with atypia was also around 53%-63% [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue is that the diagnosis of cytology depends on the experience of pathologists and has the inter-institutional variability. Although the risk of malignancy (ROM) of AUS (atypia of undetermined significance) in the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) was only 20%, several studies showed that their ROM of AUS was higher than 20%, around 47–50% [ 15 , 16 , 17 ]. Before the proposal of Milan system, the ROM of cytological report with atypia was also around 53%-63% [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A score of 1 represents almost soft (almost green within the lesion), a score of 2 represents mostly soft (green more than blue), a score of 3 represents mostly stiff (blue more than green), and a score of 4 represents almost stiff (almost blue). Using FNA cytology, the cytological report of atypia [ 15 , 16 , 17 , 18 , 19 ], suspicious malignancy or malignancy was classified as suspicious malignancy.…”
Section: Methodsmentioning
confidence: 99%
“…The observed rate of malignancy in our dataset is similar to the proposed risk of malignancy by the MSRSGC. These categories have been validated by multiple retrospective reviews of cytopathology reports across the globe since the introduction of the MSRSGC in 2015 6–8 . Viswanathan et al in 2018 performed a retrospective analysis of 627 salivary gland FNAs applying the MSRSGC and found strong correlation between the proposed risk of malignancy and the actual rate of malignancy after sialoadenectomy 9 .…”
Section: Discussionmentioning
confidence: 99%
“…These categories have been validated by multiple retrospective reviews of cytopathology reports across the globe since the introduction of the MSRSGC in 2015. [6][7][8] Viswanathan et al in 2018 performed a retrospective analysis of 627 salivary gland FNAs applying the MSRSGC and found strong correlation between the proposed risk of malignancy and the actual rate of malignancy after sialoadenectomy. 9 Rivera Rolon et al reviewed 208 salivary gland FNAs in 2020 that confirmed these findings and suggested a diagnostic accuracy of 94.4% when distinguishing benign versus malignant pathology.…”
Section: Discussionmentioning
confidence: 99%
“…1 FNA is a minimally invasive, relatively welltolerated, and cost-effective procedure, and it is widely accepted for differentiating non-neoplastic lesions from neoplastic lesions, and benign from malignant neoplasms. 1 The sensitivity and specificity of FNA in SGNs vary from 83% to 92% and from 93% to 100%, respectively. 3 Also, FNA provides prognostic information and ancillary molecular testing samples.…”
Section: Introductionmentioning
confidence: 99%